A seven-year study on an integrated hospital-community diabetes management program in Chinese patients with diabetes. Issue 3 (June 2018) - Chen, Siyu; Hou, Xuhong; Sun, Yu; Hu, Gang; Zhou, Xiaoyan; Xue, Huijuan; Chen, Peizhu; Wu, Jingzhu; Bao, Yuqian; Jia, Weiping
Highlights: An integrated hospital-community diabetes management program was piloted. "ABC" targets: HbA1c <7.0%, blood pressure <140/80 mmHg, and LDL-C <100 mg/dL. Glycemic control was suboptimal in the subpopulations. BP control was ideal but high LDL-C should be given sufficient attention. Validated instruments for screening diabetic chronic complications were promoted. Abstract: Aims: To assess whether an integrated hospital-community diabetes management program could improve major cardiovascular risk factor control among patients with diabetes in real-world clinical settings. Methods: 985 adults with diabetes in the Shanghai Taopu community health service center were enrolled at baseline and 907 subjects completed the follow-up. The follow-up levels of the metabolic profiles were assessed by their averages during the follow up period. Results: After a mean 7-year follow-up period, heamoglobin A1c, systolic and diastolic blood pressure levels decreased by 0.6%, 5.7 mmHg, and 1.5 mmHg, respectively (all P < 0.001). There was a non-significant difference in low-density lipoprotein cholesterol, while high-density lipoprotein cholesterol increased 1.9 mg/dL and triglycerides decreased 28.3 mg/dL, respectively (all P < 0.001). The percentage of patients with diabetes who met any one of three Chinese Diabetes Society goals (heamoglobin A1c <7.0%, blood pressure <140/80 mmHg, and low-density lipoprotein cholesterol <100 mg/dL) increased from 58.2% to 70.1%. The chronic diabetes complication screening rates (diabetic retinopathy, diabetic neuropathy, diabetic nephropathy) have significantly increased, from almost zero to 12–78%. Conclusions: This long-term program has increased the proportions of attaining major cardiovascular risk factors control goals and diabetic chronic complication screening rates among patients with diabetes.